2022
DOI: 10.3390/molecules27238273
|View full text |Cite
|
Sign up to set email alerts
|

Tannin in Ruminant Nutrition: Review

Abstract: Tannins are polyphenols characterized by different molecular weights that plants are able to synthetize during their secondary metabolism. Macromolecules (proteins, structural carbohydrates and starch) can link tannins and their digestion can decrease. Tannins can be classified into two groups: hydrolysable tannins and condensed tannins. Tannins are polyphenols, which can directly or indirectly affect intake and digestion. Their ability to bind molecules and form complexes depends on the structure of polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 234 publications
1
43
0
Order By: Relevance
“…Many studies have demonstrated that active substances, including monoterpenoid glycosides, paeonols, flavonoids, phenols, and tannins, can improve gastrointestinal health in animals (Besharati et al, 2022; Kang et al, 2022; Pei et al, 2020; Yu et al, 2019). Meanwhile, PR had better effects on rumen fermentation, most likely due to the presence of paeonols in the PR, whereas PSL and PSM have limited paeonols and there is increasing recognition that they have a vital role in gastrointestinal health (Kang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have demonstrated that active substances, including monoterpenoid glycosides, paeonols, flavonoids, phenols, and tannins, can improve gastrointestinal health in animals (Besharati et al, 2022; Kang et al, 2022; Pei et al, 2020; Yu et al, 2019). Meanwhile, PR had better effects on rumen fermentation, most likely due to the presence of paeonols in the PR, whereas PSL and PSM have limited paeonols and there is increasing recognition that they have a vital role in gastrointestinal health (Kang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Herbal byproducts (tea residue) altered rumen fatty acid composition and rumen microbiota and improved muscle metabolism in steers (Li et al, 2022). Furthermore, tannins affect meat fatty acid profile through rumen level modulating lipid metabolism (Besharati et al, 2022). More importantly, fatty acid metabolism is closely related to amino acid metabolism (Wallace et al, 2018); therefore, changes in amino acids in lamb meat in our studies were reasonable, although mechanisms are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations